ANTITUMOR ACTIVITY OF CRATEVA MAGNA IN TRANSPLANTABLE TUMOR MODELS IN MICE: ANTITUMOR ACTIVITY OF CRATEAVA MAGNA - ANKITA DEEP; SINDHU R; KENGANORA MRUTHUNJAYA; SANTHEPETE N MANJULA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study aims to evaluate the anticancer and immunomodulatory activity of both the alcoholic and aqueous extracts of Crateva magna (ALCM and AQCM) in solid tumor model and ascites tumor model in mice. Methods: The study was divided into in vitro and in vivo sections. In vitro, antioxidant activity of both the extracts was evaluated by well-established antioxidant assays such as α, α-diphenyl-β-picrylhydrazyl radical scavenging, reducing power, and 3-ethylbenzothiazoline-6-sulfonic acid radical scavenging. Both the extracts were subjected for in vitro preliminary cytotoxicity screening by brine shrimp lethality assay and Trypan blue exclusion assay. In vivo antitumor activity of ALCM and AQCM was assessed at the doses of 100 mg/kg and 200 mg/kg bodyweight, respectively, by Dalton’s Lymphoma ascites induced robust tumor model and Ehrlich Ascites Carcinoma induced ascites tumor model in mice. Substantial tumor volume, tumor weight, and % inhibition of the tumor weight in treated and untreated groups were evaluated. In addition to the investigation of antitumor activity, the possible immunomodulatory activity was also assessed. Results: The studies showed that the ALCM demonstrated more significant antioxidant activity. The results also showed more immunomodulatory activity when compared to AQCM. Conclusion: The study proves that the plant extract is of higher therapeutic efficacy in cancer. However, the extracts require more exploration toward its usefulness in drug discovery.